2020
DOI: 10.1155/2020/8859961
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Data Privacy Protection Scheme Based on Blockchain and Cloud Computing

Abstract: With the features of decentralization and trustlessness and through distributed data storage, point-to-point transmission, and encryption algorithms, blockchain has shed new light on the security and protection of medical data, and it can resolve the contradiction between data sharing and privacy protection with proper security strategies. In this paper, we integrate the strengths of both blockchain and cloud computing and build the privacy protection scheme for medical data based on blockchain and cloud compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In most of the blockchain-based solutions, confidentiality is maintained using cryptographic tools to ensure that data is not readable by unauthorized users [100], [107], [131]. We found that most popular encryption algorithms are Attribute-based Encryption (ABE) [91], Proxy Re-Encryption (PRE) [90], and symmetric encryption (e.g., AES) [11]. Integrity of EHR data is all about consistency and completeness, and also refers to their safety.…”
Section: Blockchain For Ehrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the blockchain-based solutions, confidentiality is maintained using cryptographic tools to ensure that data is not readable by unauthorized users [100], [107], [131]. We found that most popular encryption algorithms are Attribute-based Encryption (ABE) [91], Proxy Re-Encryption (PRE) [90], and symmetric encryption (e.g., AES) [11]. Integrity of EHR data is all about consistency and completeness, and also refers to their safety.…”
Section: Blockchain For Ehrsmentioning
confidence: 99%
“…Often, a third party who requests access to the owner of EHRs, follows a public-key encryption process [99]. For instance, ABE [91] allows third parties to get access rights from some attributes such as "doctor" and "hospital". Authorization is the process where a patient or hospital authorizes someone to get access to his EHRs.…”
Section: Blockchain For Ehrsmentioning
confidence: 99%
“…The architecture manages many access control policies and models. We use a unique EHR sharing architecture that combines aspects of blockchain and IPFS for mobile cloud computing [ 23 ]. They created an access control system to ensure EHR exchange between patients and doctors (patients and medical providers).…”
Section: Background and Related Workmentioning
confidence: 99%
“…The underlying blockchain technology network model provides a method of storing distributed data, ensuring the stability and effectiveness of the model network. Use encryption technology for digital signatures and highly encrypted account information to ensure data transmission [6] and secure access-CCP replaces third-party intermediaries [7] to provide technical support for trade security and user confidence. In the blockchain system, the data generated by the participants' transactions are packaged into a data block.…”
Section: Blockchain Technologymentioning
confidence: 99%